Determination and modification: Topology of prenominal attributes in Lithuanian - Trakymaitė, Ringailė (Kalbotyra, 2018)
[full article and abstract in English]This paper offers a description of the linear structure of the definite Lithuanian noun phrase (NP) with an emphasis on prenominal attributes. Morphological and syntactical coding of definiteness is examined through the comparison of NP structures in Lithuanian (a language with relatively ungrammaticalised marking of definiteness) and Swedish (a language with fully developed overt marking of definiteness). The special role of definite attributes, quantifiers and adjectival modifiers is shown through identifying key positions in a linear structure of the Lithuanian NP. A topology of the Lithuanian NP is then suggested reflecting the multi-layered nature of the reference-assigning process mirrored in multi-exponential marking of definiteness, with adjectival marking being a very important one. Variations in NP structures are described using Lithuanian and Swedish data focusing on the combinatorial possibilities of definite adjectival modifiers and other determiners.
Keywords: adjective; genitive; definiteness; demonstrative; determinative; noun phrase; quantifier; prenominal